Uneasy heads: the play of law and history in Brenton's 55 Days. Issue 1 (2nd January 2016) - Ward, Ian
Abstract : Howard Brenton's 55 Days was first performed at the Hampstead Theatre in October 2012. Its subject matter is the events which led up to the execution of King Charles I on 30 January 1649. The title of the play alludes to the purging of Parliament fifty-five days earlier. Pride's Purge, as it became known, removed those Presbyterian MPs who had signalled their opposition to the mooted idea of bringing the defeated king to trial. The first part of this article will revisit the events of autumn and winter 1648-49. The second part will then examine Brenton's particular treatment of this iconic moment in English constitutional history.